Effectivity of the Oketani Massage and the Back Massage Combination towards Breastmilk Production and to Prevent Breast Engorgement of Postpartum Mothers - Ayesha Hendriana Ngestiningrum; Nuryani Nuryani; Astuti Setiyani (Health Notions, 2022)
Breast milk is the most important baby food, especially during the first weeks of a baby's life. To help postpartum mothers with breastfeeding problems and breast engorgement, the researchers developed a combination of Oketani massage and back massage to increase breastmilk production and to prevent breast engorgement. This was quasi-experimental research designed with a pretest-posttest and with a control group. The research population consisted of post-partum mothers in the Lembeyan Community Health Center area, Magetan Regency, East Java with a consecutive sampling technique. The respondents consisted of 50 people. The independent variable was the combination of the Oketani Massage and the Back Massage, meanwhile, the dependent variables were breastmilk production and prevention of breast engorgement in postpartum mothers. The combination of the Oketani Massage and Back Massage was effective in increasing breastmilk production. This could be seen from the results of the independent t-test with a significance value of 0.00 (less then 0.05). To determine the effectiveness of massage combinations to prevent breast engorgement, the researcher used the Chi-square test, which resulted in a significant value of 0.011 (less then 0.05). The combination of the Oketani massage and back massage is effective in increasing breast milk production as well as preventing breast engorgement. Keywords: combination; oketani massage; back massage; breastmilk production; breast engorgement